2016
DOI: 10.1177/0093854816655837
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Public Attitudes Toward Ex-Offenders

Abstract: Ex-offenders face barriers to community reintegration including negative attitudes held by members of the public. This meta-analysis summarizes the extant research on the correlates of public attitudes toward ex-offenders—namely, public, ex-offender, and community characteristics—and the moderating effects of sexual offense history. A systematic search of four databases (PsycINFO, Web of Science, National Criminal Justice Reference Service [NCJRS], and ProQuest Dissertation & Theses) identified 19 records,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
107
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 56 publications
9
107
2
Order By: Relevance
“…Their results showed significant effect sizes whereby people tend to make automatic character inferences and judgments about the guilt and trustworthiness of defendants based solely on their appearances. Various research findings have showed that people do tend to make negative associations and to support cultural stereotypes based on extralegal factors (e.g., social class, tattoos, race, gender) and that this does have an impact on how people are viewed and treated by others (Funk & Todorov, 2013;Rade, Desmarais, & Mitchell, 2016). One way to reduce these negative ways of thinking about those from out-groups is to increase one's contact and positive relations with those members.…”
Section: Grounding In the Pertinent Literaturementioning
confidence: 99%
“…Their results showed significant effect sizes whereby people tend to make automatic character inferences and judgments about the guilt and trustworthiness of defendants based solely on their appearances. Various research findings have showed that people do tend to make negative associations and to support cultural stereotypes based on extralegal factors (e.g., social class, tattoos, race, gender) and that this does have an impact on how people are viewed and treated by others (Funk & Todorov, 2013;Rade, Desmarais, & Mitchell, 2016). One way to reduce these negative ways of thinking about those from out-groups is to increase one's contact and positive relations with those members.…”
Section: Grounding In the Pertinent Literaturementioning
confidence: 99%
“…On the one hand, citizens support the general notion of providing services to help prepare individuals for release and to facilitate reintegration (Garland, Wodahl, and Cota, ; Garland, Wodahl, and Saxon, ; Garland, Wodahl, and Schuhmann, ; Jonson and Cullen, ; Ouellette, Applegate, and Vuk, ; Sundt, Cullen, Thielo, and Jonson, ; Thielo, Cullen, Cohen, and Chouhy, ). On the other hand, the willingness to support the distribution of services depends on the characteristics of the population receiving services (Garland et al., , ; Ouellette et al., ; Rade, Desmarais, and Mitchell, ), the proximity of where services will be delivered in relation to respondents’ residences (Garland et al., , , ; Rade et al., ), and the public finances employed to provide services (Garland et al., ). Furthermore, the public is hesitant to provide services to reentrants if other individuals without criminal records are also in need of similar forms of assistance (Garland et al., ; Immerwhar and Johnson, ).…”
mentioning
confidence: 99%
“…As all of these authors indicate, the public is reluctant to support emergency or temporary housing placements for individuals released from prison, is averse to improve the conditions of such placements, and does not want reentrants to reside near their households. This is especially true for individuals convicted of sex offenses (Garland et al., , ; Harris and Socia, ; King and Roberts, ; Mancini and Pickett, ; Rade et al., ). Yet, local governments need to place individuals somewhere; no city, town, or municipality wants to be known for homeless encampments (see Herring, ).…”
mentioning
confidence: 99%
“…One such sect of stigmatized persons includes criminal offenders given their linkage as being social deviants, especially registered sex offenders (RSOs). In support of this argument, offenders who have committed sex crimes experience stigma that is above and beyond those without the sex offender label (Hipp, Turner, & Jannetta, 2010;Rade, Desmarais, & Mitchell, 2016;see Tewksbury, 2012;Tewksbury & Lees, 2006). Some registered sex offenders have self-imposed an isolated lifestyle that is then exacerbated by the stigma associated with their sex offender status (Burchfield & Mingus, 2008).…”
mentioning
confidence: 99%
“…"Normals" (or the public, assuming that they are without a sexual conviction history) hold a greater negative attitude toward RSOs than ex-offenders without sexual convictions (Rade et al, 2016). Correspondently, RSOs have reported feelings of inferiority and ostracism when among the general populace (Burchfield & Mingus, 2008;Evans & Cubellis, 2015;Levenson & Cotter, 2005;Levenson, D'Amora, & Hern, 2007b;Mustaine & Tewksbury, 2011a; see Tewksbury, 2012;Tewksbury & Lees, 2006;Zevitz & Farkas, 2000b).…”
mentioning
confidence: 99%